Composite material, preparation method thereof and luminescent device

By using N -type metal oxide and negative electrical organic group modified quantum dot to prepare composite materials, the problem of insufficient electronic transmission and injection performance of quantum dot luminous devices in existing technologies has been solved, and efficient electronic transmission and injection are realized , Improve the lighting efficiency and stability.

CN119371956APending Publication Date: 2025-01-28GUANGDONG JUHUA RES INST OF ADVANCED DISPLAY
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202310935574.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-07-27
Publication Date
2025-01-28

AI Technical Summary

Technical Problem

The application range of existing quantum dot light emitting devices is relatively single, and it is difficult to achieve the improvement of light emitting performance and electron transmission and injection performance at the same time.

Method used

A composite material, which is composed of a quantum dot of the N -type metal oxide and the surface connected to the surface of organic groups with negative electrical groups. Through specific preparation methods, including light treatment and the addition of organic metal salt, it forms excellent electronics with excellent electronics Composite materials for transmission and injection performance.

Benefits of technology

The high -efficiency electron transmission and injection of composite materials in the luminous devices is realized, which improves the lighting efficiency and the stability of the device, and at the same time, it has good film formation.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119371956A_ABST
    Figure CN119371956A_ABST
Patent Text Reader

Abstract

The invention discloses a composite material, a preparation method thereof and a light-emitting device. The composite material provided by the invention comprises an n-type metal oxide and quantum dots, the surfaces of the quantum dots are connected with organic groups with electronegativity, and the composite material has relatively good luminescence performance and electron transmission and electron injection performance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the field of display technology, and in particular to a composite material and a preparation method thereof, and a light-emitting device. Background Art

[0002] Quantum dots (QD) are semiconductor nanostructures that bind conduction band electrons, valence band holes and excitons in three spatial directions. Due to their wide excitation spectrum, narrow half-width, tunable wavelength and solution processing, quantum dots have been used as luminescent materials and in the luminescent layer of quantum dot light-emitting devices.

[0003] However, the current application scope of quantum dots is relatively single, such as luminescence. How to improve the wide application of quantum dots is a major research direction for quantum dot applications. Summary of the invention

[0004] In view of this, the present application provides a composite material and a preparation method thereof, a light-emitting device and a display device, aiming to provide a composite material having light-emitting properties while also having good electron transport and electron injection properties.

[0005] The embodiments of the present application are implemented as follows: In a first aspect, a composite material is provided, comprising an n-type metal oxide and quantum dots, wherein the surface of the quantum dots is connected to a negatively charged organic group;

[0006] Wherein, the organic group includes one or more of the following structural formulas:

[0007]

[0008] Wherein, each occurrence of R1, R2, R3, and R4 is independently selected from one or more of H, D, -NH2, C1-C30 alkyl, aryl having 5-30 ring atoms, heteroaryl having 5-30 ring atoms, and C1-C30 alkyl substituted by at least one of -NO2, -CN, -NH2, -OH, -X, and C1-C5 alkyl, aryl having 5-30 ring atoms substituted by at least one of -NO2, -CN, -NH2, -OH, -X, and C1-C5 alkyl, and heteroaryl having 5-30 ring atoms substituted by at least one of -NO2, -CN, -NH2, -OH, -X, and C1-C5 alkyl.

[0009] Accordingly, an embodiment of the present application further provides a method for preparing a composite material, comprising: providing a first mixture, wherein the first mixture comprises quantum dots and a first solvent, wherein the first solvent comprises a hole sacrificial agent; after subjecting the first mixture to a first light treatment, an organic metal salt is added to the first mixture, and the second light treatment is continued to be performed to obtain a composite material; wherein the organic metal salt comprises an organic anion and a metal ion, and the organic anion comprises one or more of the following structural formulas:

[0010]

[0011] Wherein, each occurrence of R1, R2, R3, and R4 is independently selected from one or more of H, D, -NH2, C1-C10 alkyl, aryl having 5-24 ring atoms, heteroaryl having 5-24 ring atoms, and C1-C10 alkyl substituted by at least one of -NO2, -CN, -NH2, -OH, -X, and C1-C5 alkyl, aryl having 5-24 ring atoms substituted by at least one of -NO2, -CN, -NH2, -OH, -X, and C1-C5 alkyl, and heteroaryl having 5-24 ring atoms substituted by at least one of -NO2, -CN, -NH2, -OH, -X, and C1-C5 alkyl, and X is a halogen; and the metal ions include metal ions capable of forming n-type metal oxides.

[0012] In a third aspect, an embodiment of the present application further provides a light-emitting device, comprising: a first electrode and a second electrode arranged opposite to each other; a second light-emitting layer, arranged between the first electrode and the second electrode; wherein the material of the second light-emitting layer comprises the above-mentioned composite material, or comprises a composite material obtained by the preparation method of the above-mentioned composite material.

[0013] In a fourth aspect, an embodiment of the present application further provides a display device, comprising the light-emitting device as described above.

[0014] The present application provides a composite material, comprising an n-type metal oxide and quantum dots, wherein the surface of the quantum dots is connected with negatively charged organic groups and has good electron transport performance and electron injection performance. BRIEF DESCRIPTION OF THE DRAWINGS

[0015] In order to more clearly illustrate the technical solutions in the embodiments of the present application, the drawings required for use in the description of the embodiments will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present application. For those skilled in the art, other drawings can be obtained based on these drawings without creative work.

[0016] Figure 1It is a schematic flow chart of an embodiment of a method for preparing a composite material provided in the present application;

[0017] Figure 2 A structural schematic diagram of an embodiment of a light emitting device is provided for the present application.

[0018] Figure 3 A schematic diagram of a process of an embodiment of a method for preparing a light-emitting device provided in the present application;

[0019] Figure 4 A schematic diagram of another embodiment of a method for preparing a light-emitting device provided in the present application;

[0020] Figure 5 EQE-J diagrams of device embodiments 1-8 and device comparative example 1;

[0021] Figure 6 EQE-J diagrams of device examples 8 and 9 and device comparative example 2;

[0022] Figure 7 EQE-J diagrams of device examples 11 and 12 and device comparative example 3;

[0023] Figure 8 EQE-J diagrams of device embodiments 2, 13-17 and device comparative example 1.

[0024] Reference numerals: light emitting device 100 ; first electrode 10 ; second electrode 20 ; light emitting layer 30 , first light emitting layer 31 , second light emitting layer 32 ; electron functional layer 40 , electron injection layer 41 , electron transport layer 42 ; hole functional layer 50 , hole injection layer 51 , hole transport layer 52 . DETAILED DESCRIPTION

[0025] The following will be combined with the drawings in the embodiments of the present application to clearly and completely describe the technical solutions in the embodiments of the present application. Obviously, the described embodiments are only part of the embodiments of the present application, not all of the embodiments. Based on the embodiments in the present application, all other embodiments obtained by those skilled in the art without creative work belong to the scope of protection of the present application. In addition, it should be understood that the specific implementation methods described herein are only used to illustrate and explain the present application, and are not used to limit the present application. In the present application, unless otherwise specified, the directional words such as "upper" and "lower" used are specifically the directions of the drawings in the accompanying drawings. In addition, in the description of the present application, the term "including" means "including but not limited to". Various embodiments of the present invention may exist in the form of a range; it should be understood that the description in the form of a range is only for convenience and simplicity, and should not be understood as a rigid limitation on the scope of the present invention; therefore, it should be considered that the range description has specifically disclosed all possible sub-ranges and single values ​​within the range. For example, description of a range from 1 to 6 should be considered to have specifically disclosed sub-ranges, such as from 1 to 3, from 1 to 4, from 1 to 5, from 2 to 4, from 2 to 6, from 3 to 6, etc., as well as single numbers within the stated range, such as 1, 2, 3, 4, 5, and 6, regardless of the range. In addition, whenever a numerical range is indicated herein, it is meant to include any cited numeral (fractional or integral) within the stated range.

[0026] In this application, "and / or" describes the association relationship of associated objects, indicating that there may be three relationships. For example, A and / or B can mean: A exists alone, A and B exist at the same time, and B exists alone. A and B can be singular or plural.

[0027] In the present application, "at least one" means one or more, and "plurality" means two or more. "At least one", "at least one of the following" or similar expressions refer to any combination of these items, including any combination of single items or plural items. For example, "at least one of a, b, or c", or "at least one of a, b, and c" can all mean: a, b, c, ab (i.e., a and b), ac, bc, or abc, where a, b, c can be single or multiple, respectively.

[0028] The present application provides a composite material, comprising an n-type metal oxide and quantum dots, wherein the surface of the quantum dots is connected to a negatively charged organic group, wherein the organic group comprises one or more of the following structural formulas:

[0029]

[0030] Wherein, each occurrence of R1, R2, R3, and R4 is independently selected from one or more of H, D, -NH2, C1-C30 alkyl, aryl having 5-30 ring atoms, heteroaryl having 5-30 ring atoms, and C1-C30 alkyl substituted by at least one of -NO2, -CN, -NH2, -OH, -X, and C1-C5 alkyl, aryl having 5-30 ring atoms substituted by at least one of -NO2, -CN, -NH2, -OH, -X, and C1-C5 alkyl, and heteroaryl having 5-30 ring atoms substituted by at least one of -NO2, -CN, -NH2, -OH, -X, and C1-C5 alkyl; X is halogen selected from one or more of F, Cl, Br, and I.

[0031] It can be understood that the aromatic group having 5-30 ring atoms substituted by at least one of -NO2, -CN, -NH2, -OH, -X, and C1-C5 alkyl specifically means that the H on the aromatic group having 5-30 ring atoms can be replaced by one or more of hydroxyl, -NO2, -CN, -NH2, -OH, -X, and C1-C5 alkyl.

[0032] It can be understood that the number of carbon atoms in the C1-C30 alkyl, the aryl having 5-30 ring atoms, and the alkyl, aryl or heteroaryl in the heteroaryl having 5-30 ring atoms can be 1, 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, 13, 14, 15, 16, 17, 18, 19, 20, 21, 22, 23, 24, 25, 26, 27, 28, 29, or 30.

[0033] Further, in one embodiment, each occurrence of R1, R2, R3, and R4 is independently selected from -NH2, C1-C10 alkyl, C1-C10 alkyl substituted by at least one of -NO2, -CN, -NH2, -OH, -X, and C1-C5 alkyl, and aryl having 5-24 ring atoms substituted by at least one of -NO2, -CN, -NH2, -OH, -X, and C1-C5 alkyl.

[0034] Among them, the aromatic group with 5-24 ring atoms can be selected from one or more combinations of phenyl, naphthyl, biphenyl, etc.; the heteroaryl group with 5-30 ring atoms can be selected from one or more combinations of imidazolyl, pyridyl, pyrrolyl, pyrimidinyl, thiophene, quinolyl, indolyl, furanyl, etc.; the C1-C10 alkyl group can be selected from one or more combinations of methyl, ethyl, n-propyl, isopropyl, n-butyl, etc.

[0035] In a specific embodiment, each occurrence of R1, R2, R3, and R4 is independently selected from methyl, ethyl, n-propyl, isopropyl, n-butyl, phenyl, naphthyl, biphenyl, pyridyl, benzopyridyl, pyrimidyl, benzopyrimidyl, amino, and one or more of methyl, ethyl, n-propyl, isopropyl, n-butyl, phenyl, naphthyl, biphenyl, pyridyl, and pyrimidyl substituted with at least one of -OH, -X, methyl, ethyl, n-propyl, isopropyl, and n-butyl; X is halogen selected from one or more of F, Cl, Br, and I.

[0036] In one embodiment, R1 is selected from one or more of -NH2, -CH3, -CH2CH3, -CH2F, -CHF2, -CF3, phenyl, naphthyl, biphenyl, and tolyl.

[0037] In one embodiment, R2, R3, and R4 are independently selected from one or more of -CH3, -CH2CH3, -CH2F, -CHF2, -CF3, phenyl, naphthyl, biphenyl, and tolyl.

[0038] In one embodiment, each occurrence of R1, R2, R3, and R4 is independently selected from the following groups:

[0039]

[0040] In the present application, "*" indicates a connection site or a fusion site. When the connection site is not specified in the group, it means that an optional connection site in the group is used as the connection site. When the fusion site is not specified in the group, it means that an optional fusion site in the group is used as the fusion site.

[0041] In one embodiment, the organic group may include one or more of the following structural formulas:

[0042]

[0043] It is understood that the enol form can exist in the keto form, i.e. Can also

[0044] In this embodiment, the n-type metal oxide belongs to an n-type semiconductor material, which is a semiconductor material that is mainly electronically conductive. That is, there are two types of carriers in the n-type metal oxide, namely, holes in the valence band and electrons in the conduction band, but electronic conductivity is the main one.

[0045] The composite material of this embodiment includes the n-type metal oxide and the quantum dots with the organic groups connected to the surface, and has good luminescence performance, electron transport and electron injection performance, and film-forming property.

[0046] Specifically, in the composite material, the organic group containing sulfonic acid, carboxyl, acyl and other groups is connected to the surface of the quantum dot. On the one hand, it can fill a large number of empty orbits on its surface and passivate the surface defects of the quantum dots (such as oxygen vacancy defects) as a ligand, thereby improving the luminescence performance of the quantum dots and improving the dispersibility and film-forming properties of the composite material; on the other hand, it can enhance the electron injection performance, thereby improving carrier recombination, improving luminescence efficiency and other properties.

[0047] In one embodiment, the n-type metal oxide is connected to the quantum dot. Specifically, the n-type metal in the n-type metal oxide occupies the metal vacancies on the surface of the quantum dot. Further, the n-type metal oxide is connected to the quantum dot in the form of particles. Specifically, the average particle size of the n-type metal oxide can range from 3 to 10 nm, specifically 3 to 5 nm, 5 to 10 nm, 3 to 8 nm, 5 to 8 nm, 8 to 10 nm, etc. The average particle size of the quantum dot can range from 2 to 15 nm, specifically 2 to 13 nm, 5 to 13 nm, 5 to 10 nm, 8 to 10 nm, etc.

[0048] In one embodiment, the n-type metal oxide includes a doped or undoped first metal oxide, the undoped first metal oxide includes one or more of zinc oxide, titanium dioxide, and tin dioxide, the doped first metal oxide includes the undoped first metal oxide and a doping element, and the doping element includes one or more of Mg, Ca, Li, Ga, Al, Co, Mn, Zr, W, Ti, and Y.

[0049] In one embodiment, the molar ratio of the doping element to the first metal oxide may be (0.05-5):100, specifically (0.05-1):100, (1-2):100, (2-3):100, (3-4):100, (4-5):100, etc.

[0050] In one embodiment, the n-type metal oxide is selected from zinc oxide. In another embodiment, the n-type metal oxide is selected from Mg-doped zinc oxide (ZMO).

[0051] The quantum dot luminescent material can be selected from at least one of a single structure quantum dot, a core-shell structure quantum dot and a perovskite semiconductor material. The single structure quantum dot is selected from at least one of a II-VI group compound, a IV-VI group compound, a III-V group compound and a I-III-VI group compound. The II-VI group compound is selected from CdS, CdSe, CdTe, ZnS, ZnSe, ZnTe, ZnO, HgS, HgSe, HgTe, CdSeS, CdSeTe, CdSTe, ZnSeS, ZnSeTe, ZnSTe, HgSeS, HgSeTe, HgSTe, CdZnS, CdS At least one of dZnSe, CdZnTe, CdHgS, CdHgSe, CdHgTe, HgZnS, HgZnSe, HgZnTe, CdZnSeS, CdZnSeTe, CdZnSTe, CdHgSeS, CdHgSeTe, CdHgSTe, HgZnSeS, HgZnSeTe and HgZnSTe, and the IV-VI group compound is selected from SnS, SnSe, SnTe, PbS, PbSe, PbTe, SnSeS, SnSeTe, SnSTe, PbSeS, PbSeTe, PbSTe, SnPbS, SnPbSe, Sn At least one of PbTe, SnPbSSe, SnPbSeTe, and SnPbSTe, and the III-V compound is selected from GaN, GaP, GaAs, GaSb, AlN, AlP, AlAs, AlSb, InN, InP, InAs, InSb, GaNP, GaNAs, GaNSb, GaPAs, GaPSb, AlNP, AlNAs, AlNSb, AlPAs, AlPSb, InNP, InNAs, InNSb, InPAs, InPSb, GaAlNP, GaAlNAs, GaAlNSb, GaAlPAs, GaAlPSb , at least one of GaInNP, GaInNAs, GaInNSb, GaInPAs, GaInPSb, InAlNP, InAlNAs, InAlNSb, InAlPAs and InAlPSb, the I-III-VI group compound is selected from at least one of CuInS, CuInSe and AgInS; the core of the quantum dots with core-shell structure is selected from any one of the above-mentioned single-structure quantum dots, and the shell material of the quantum dots with core-shell structure is selected from at least one of CdS, CdTe, CdSeTe, CdZnSe, CdZnS, CdSeS, ZnSe, ZnSeS and ZnS.

[0052] The perovskite semiconductor material is selected from doped or undoped inorganic perovskite semiconductors, or organic-inorganic hybrid perovskite semiconductors; the inorganic perovskite semiconductor has a general structural formula of AMX3, wherein A is Cs + ion, M is a divalent metal cation selected from Pb 2+ Sn 2+ , Cu 2+ 、Ni 2+ 、Cd 2+ Cr 2+ , Mn 2+ 、Co 2+ , Fe 2+ ,Ge 2+ , Yb 2+ 、Eu 2+ At least one of, X is a halogen anion selected from Cl - Br - ,I - At least one of the following; the general structural formula of the organic-inorganic hybrid perovskite semiconductor is BMX3, wherein B is an organic amine cation selected from CH3(CH2) n-2 NH3 + or [NH3(CH2) n NH3] 2+ , where n≥2, M is a divalent metal cation selected from Pb 2+ Sn 2+ , Cu 2+ 、Ni 2+ 、Cd 2+ Cr 2+ , Mn 2+ 、Co 2+ , Fe 2+ ,Ge 2+ , Yb 2+ 、Eu 2+ At least one of, X is a halogen anion selected from Cl - Br - ,I - When n=2, the inorganic metal halide octahedron MX6 4- The metal cation M is located at the center of the halogen octahedron, and the organic amine cation B fills the gap between the octahedrons to form an infinitely extended three-dimensional structure. When n>2, the inorganic metal halide octahedron MX6 connected by the top-sharing method 4- It extends in two dimensions to form a layered structure, with an organic amine cation bilayer (protonated monoamine) or an organic amine cation monolayer (protonated diamine) inserted between the layers, and the organic layer and the inorganic layer overlap to form a stable two-dimensional layered structure.

[0053] In one embodiment, the quantum dot hair may include one or more of red quantum dots, green quantum dots, and blue quantum dots. In a specific embodiment, the quantum dots may be selected from oily quantum dots.

[0054] In one embodiment, the surface of the n-type metal oxide is also connected with the organic group.

[0055] In one embodiment, the mass ratio of the n-type metal oxide to the quantum dots is (10-50):100, and specifically can be (10-45):100, (15-45):100, (15-40):100, (20-40):100, (20-35):100, (25-35):100, (25-30):100, etc. The mass ratio enables the composite material to have good luminescence performance, good electron injection and transport performance, and good film forming properties.

[0056] The present application also provides a method for preparing a composite material, see Figure 1 , Figure 1 This is a schematic flow chart of an embodiment of a method for preparing a composite material provided by the present application, which specifically includes the following steps:

[0057] Step S11: providing a first mixture, wherein the first mixture includes quantum dots and a first solvent;

[0058] Step S12: After the first mixture is subjected to the first light irradiation treatment, an organic n-type metal salt is added to the first mixture, and the second light irradiation treatment is continued to obtain a composite material.

[0059] The organic metal salt includes an organic anion and a metal ion, the metal ion includes a metal ion capable of forming an n-type metal oxide, and the organic anion can refer to the relevant description of the organic group mentioned above, which will not be repeated here.

[0060] In this embodiment, the first mixture is subjected to a first light irradiation treatment, and the quantum dots can excite electrons (e - ), the electrons can react with the oxygen and water in the first mixture system to generate hydroxides, and after the first organic metal salt is added to the system, the metal ions in the organic metal salt can react with the hydroxides to generate n-type metal oxides, and the second light treatment is continued, which can continuously promote the generation of electrons and improve the efficiency of the photocatalytic reaction. The method of this embodiment can generate n-type metal oxides in situ and improve the binding property of n-type metal oxides and quantum dots. The reaction mechanism can be referred to as follows:

[0061]

[0062] In this embodiment, the n-type metal oxide formed by the organic metal salt has good electron transport and electron injection properties, so that the composite material has luminescent properties, good electron transport and injection properties, and good film-forming properties. When the composite material is used in a light-emitting device, it can improve the surface flatness of the corresponding functional layer, reduce interface reactions, and improve the luminous efficiency of the light-emitting device.

[0063] Furthermore, the organic anions in the organic metal salt can be connected to the surface of the quantum dots and the surface of the catalytically generated n-type metal oxide, thereby reducing the surface defects of the quantum dots and the n-type metal oxide, thereby effectively avoiding the regrowth and agglomeration of the n-type metal oxide nanoparticles and the quantum dot particles, and improving the uniformity and film-forming properties of the particles in the composite material.

[0064] In addition, during the light treatment process, the holes (h+) generated by photocatalysis can also effectively fill the defects on the surface of n-type metal oxides and quantum dots (such as oxygen vacancies, etc.), play a role in passivating n-type metal oxides and quantum dots, and can effectively avoid the regrowth of n-type metal oxide nanoparticles and the quantum dot particles, improve the uniformity of the particles in the composite material, reduce agglomeration, and thus improve the film-forming property of the composite material.

[0065] In the step S11:

[0066] The quantum dots can refer to the related description of the composite material mentioned above, which will not be described here.

[0067] In one embodiment, the concentration of the quantum dots in the first mixture is 10-40 mg / mL, specifically 15-40 mg / mL, 15-35 mg / mL, 20-35 mg / mL, 20-30 mg / mL, 25-30 mg / mL, etc.

[0068] The first solvent can be selected from non-polar organic solvents, such as C1-C5 halogenated alkanes, C5-C18 alkanes, C5-C18 olefins, C5-C18 fatty acids, and C5-C18 amine solvents, wherein the C1-C5 halogenated alkanes include one or more of chloroform, dichloromethane, etc.; the C5-C18 alkanes include one or more of octadecane, dodecane, decane, n-octane, n-heptane, and cyclopentane; the C5-C18 olefins include one or more of octadecene, dodecene, decaene, octene, etc.; the C5-C18 fatty acids include one or more of decadecanoic acid, undecenoic acid, tetradecanoic acid, oleic acid, and octadecanoic acid (stearic acid); the C5-C18 amine solvents include one or more of oleylamine, octadecylamine, and octylamine.

[0069] In one embodiment, the first solution further includes a hole sacrificial agent, which can consume holes generated by photocatalysis, thereby providing more electrons to generate hydroxide.

[0070] Furthermore, the hole sacrificial agent may include one or more of acetonitrile, triethylamine, triethanolamine, sodium sulfite, methanol, ethanol, lactic acid, and the like.

[0071] In one embodiment, the mass ratio of the hole sacrificial agent to the quantum dots may be (0.5-1.5):5, specifically (0.5-1.3):5, (0.8-1.3):5, (0.8-1.0):5, (0.5-0.8):5, (1.3-1.5):5, etc. The mass ratio can provide an excess of the hole sacrificial agent to consume the holes generated in the photocatalytic reaction, and also avoid the waste of the hole sacrificial agent.

[0072] In step S12:

[0073] In one embodiment, an organic metal salt is added to the first mixture, wherein the mass ratio of the organic metal salt to the quantum dots is (1-3):5, i.e., (20-60):100, and specifically can be (20-55):100, (25-55):100, (25-50):100, (30-50):100, (30-45):100, (35-45):100, (35-40):100, etc. The mass ratio can provide enough of the organic metal salt to form an n-type metal oxide, thereby improving the film-forming property of the composite material, so that the composite material has good luminescence performance and good electron transport and injection performance.

[0074] In one embodiment, the metal ions may include zinc ions (Zn 2+ ), titanium ions (Ti 4+ ), tin ions (Sn 4+ ). In a specific embodiment, the organic metal salt includes an organic zinc salt, which may specifically include one or more of zinc p-toluenesulfonate, zinc trifluoromethanesulfonate, zinc trifluoromethanesulfonyl imide, difluoromethylsulfonyl zinc, zinc acetylacetonate, etc. In a specific embodiment, the organic metal salt includes an organic titanium salt, which may specifically include one or more of triisopropoxychlorotitanium, tetrakis(2,4-pentanedione)titanium(IV), etc. In a specific embodiment, the organic metal salt includes an organic tin salt, which may specifically include one or more of tin trifluoromethanesulfonate, tin methanesulfonate, tin acetylacetonate, etc.

[0075] It is understandable that, in one embodiment, when the n-type metal oxide is doped, that is, the n-type metal oxide is a doped first metal oxide, wherein the doped first metal oxide includes the undoped first metal oxide and a doping element, and the doping element includes one or more of Mg, Ca, Li, Ga, Al, Co, Mn, Zr, W, Ti, Y, etc. Correspondingly, the organic metal salt corresponding to the n-type metal oxide also includes a doped metal salt corresponding to the doping element. It is understandable that the metal ions may also include doped metal ions, such as Mg. 2+ , Ca 2+ , Li + , Ga 3+ 、Al 3+ 、Co 2+ , Mn 2+ 、Zr 2+ , W 6+ 、Ti 4+ , Y + One or more of the following,

[0076] In one embodiment, the organic metal salt is added to the first mixture in the form of a solution. Specifically, the second solvent corresponding to the organic metal salt may include one or more of water, alcohol solvents, ether solvents, tetrahydrofuran, acetone, chlorobenzene, and toluene. Specifically, the alcohol solvent includes one or more of methanol, ethanol, ethylene glycol, isopropanol, and n-butanol. The ether solvent includes one or more of methyl ether and ethyl ether.

[0077] In one embodiment, the organic metal salt is added while the first mixture is in a stirring state to improve the mixing uniformity of the first mixture and the organic metal salt, thereby promoting the generation of the n-type metal oxide.

[0078] In one embodiment, the time of the first light treatment is 1 to 2 hours, specifically 1 to 1.5 hours, 1.5 to 2 hours, etc. In one embodiment, the first light treatment can be full-spectrum light treatment, that is, full-band irradiation is adopted. In another embodiment, the wavelength range of the first light treatment is 200 to 2500nm, such as one or more of 200 to 380nm, 380 to 760nm, 760 to 2500nm, etc. In a specific embodiment, the first light treatment may include one or more of the ultraviolet light band (UV for short, wavelength 200 to 380nm), the visible light band (VL for short, wavelength 380 to 760nm) or the infrared light band (IR for short, wavelength 760 to 2500nm). In this embodiment, the light source of the first light treatment can be a single light source or a composite light source formed by multiple light sources. In a specific embodiment, the light source of the first light treatment is a xenon (Xe) lamp. Specifically, the power of the Xe lamp may be 200-500W, such as 200-300W, 300-400W, 400-500W, etc.

[0079] In one embodiment, during the first light irradiation process, the first mixture is in a stirring state to improve mixing uniformity, improve light irradiation uniformity, and improve heat dissipation.

[0080] In one embodiment, during the first light treatment of the first mixture, the temperature of the first mixture is maintained at 0-30°C, such as 0-4°C, 4-20°C, 20-25°C, 25-30°C, etc. Specifically, the first mixture can be protected by circulating condensed water to control the temperature of the first mixture within a preset range to avoid excessive temperature of the first mixture due to heat generation from light.

[0081] The second light irradiation time is 2 to 4 hours, specifically 2 to 3.5 hours, 2.5 to 3.5 hours, 2.5 to 3 hours, 2 to 2.5 hours, 3.5 to 4 hours, etc. The second light irradiation time range can photocatalytically obtain the preset loading of the n-type metal oxide.

[0082] In one embodiment, the second light treatment is full-spectrum light treatment, that is, full-band irradiation is used. In another embodiment, the wavelength range of the second light treatment is 200-2500nm, such as one or more of 200-380nm, 380-760nm, 760-2500nm, etc. In one embodiment, the second light treatment may include one or more of ultraviolet light band (UV for short, wavelength 200-380nm), visible light band (VL for short, wavelength 380-760nm) or infrared light band (IR for short, wavelength 760-2500nm). In this embodiment, the light source of the second light treatment can be a single light source or a composite light source formed by multiple light sources. In a specific embodiment, the light source of the second light treatment is a xenon (Xe) lamp. Specifically, the power of the Xe lamp can be 200-500W, such as 200-300W, 300-400W, 400-500W, etc.

[0083] In one embodiment, an organic metal salt is added to the first mixture to obtain a second mixture, and a second light treatment is continued. During the second light treatment of the second mixture, the temperature of the second mixture is maintained at 0 to 30°C, such as 0 to 4°C, 4 to 20°C, 20 to 25°C, 25 to 30°C, etc. Specifically, the second mixture can be protected by circulating condensed water to control the temperature of the second mixture within a preset range to avoid excessive temperature of the second mixture due to heat generation from light, thereby avoiding damage to the quantum dots.

[0084] In one embodiment, an organic metal salt is added to the first mixture to obtain a second mixture, and during the second light irradiation treatment, the second mixture may be in a stirring state to improve mixing uniformity and increase the rate of generating n-type metal oxide.

[0085] In one embodiment, after the second light treatment, the method further includes: using a cleaning agent to perform sedimentation washing on the mixture N times, where N is an integer greater than or equal to 2, such as washing three times. The cleaning agent may include one or more of ethyl acetate, n-butane, etc. In this embodiment, unreacted reactants, such as unreacted organic metal salts, etc., may be removed by multiple washings.

[0086] The present application provides a light emitting device, referring to Figure 2 , Figure 2The present application provides a schematic structural diagram of an embodiment of a light-emitting device, wherein the light-emitting device 100 includes a first electrode 10 and a second electrode 20 arranged opposite to each other, and a light-emitting layer 30 arranged between the first electrode 10 and the second electrode 20. The material of the light-emitting layer 30 includes the composite material provided in the present application, or includes a composite material prepared by the method for preparing the composite material provided in the present application.

[0087] In this embodiment, the material of the light-emitting layer 30 includes a composite material, namely, the n-type metal oxide and the quantum dots with the organic groups connected to the surface, which has good light-emitting performance and electron transport and injection performance.

[0088] Furthermore, when the organic group is connected to the surface of the quantum dot, on the one hand, it can fill a large number of empty orbitals on the surface and passivate the surface defects of the quantum dot as a ligand, thereby improving the luminescence performance of the quantum dot and improving the dispersibility and film-forming properties of the composite material; on the other hand, it can improve the electron injection performance, thereby improving carrier recombination, improving luminescence efficiency and other performances. In turn, it can improve the surface flatness, film uniformity and density of the light-emitting layer 30, reduce interface reactions, reduce and avoid leakage current of the light-emitting device 100, and improve the luminescence efficiency and stability performance of the light-emitting device 100.

[0089] In one embodiment, the material of the light-emitting layer 30 is composed of the composite material provided in the present application, or is composed of the composite material prepared by the method for preparing the composite material provided in the present application. Further, the thickness of the light-emitting layer 30 can be 20 to 30 nm, specifically 20 to 28 nm, 22 to 28 nm, 12 to 25 nm, etc.

[0090] In this embodiment, the single light-emitting layer 30 can realize electron injection and transmission as well as carrier recombination, thereby realizing the light-emitting device 100 to emit light, and the light-emitting device 100 has good light-emitting efficiency.

[0091] In another embodiment, the light-emitting layer 30 includes a first light-emitting layer 31 and a second light-emitting layer 32, wherein the first light-emitting layer 31 is arranged close to the first electrode 10, the material of the first light-emitting layer 31 is a first quantum dot, the second light-emitting layer 32 is arranged close to the second electrode 20, and the second light-emitting layer 32 is composed of the composite material provided in the present application, or, is composed of a composite material prepared by the preparation method of the composite material provided in the present application.

[0092] In one embodiment, the sum of the thickness of the second light-emitting layer 32 and the first light-emitting layer 31 is 20-50 nm, specifically 20-45 nm, 25-45 nm, 25-40 nm, 30-40 nm, 30-35 nm, etc. Further, the thickness of the first light-emitting layer 31 is 10-20 nm, specifically 10-18 nm, 12-18 nm, 12-15 nm, etc. The thickness of the second light-emitting layer 32 is 20-30 nm, specifically 20-28 nm, 22-28 nm, 22-25 nm, etc.

[0093] In one embodiment, the type of the first quantum dots is the same as the type of quantum dots in the composite material in the second light-emitting layer. In this embodiment, through the two-layer structure of the light-emitting layer 30, the second light-emitting layer 32 is composed of the composite material. Since the type of quantum dots in the second light-emitting layer 32 and the first light-emitting layer 31 is the same, the two layers have good contact or compatibility, reducing the negative impact of the interface on electron injection and transmission, thereby improving the luminous efficiency of the light-emitting device 100.

[0094] In one embodiment, the light emitting device 100 includes an electronic functional layer 40, and the electronic functional layer 40 is disposed between the second electrode 20 and the light emitting layer 30. In this embodiment, the light emitting layer 30 includes the composite material, wherein the n-type metal oxide included therein is also an electronic functional material, thereby improving the interface contact between the light emitting layer 30 and the electronic functional layer 40, reducing the negative impact of the interface on electron injection and transmission, and thus improving the luminous efficiency of the light emitting device 100.

[0095] In one embodiment, the electronic functional layer 40 is disposed between the second electrode 20 and the second light-emitting layer 32. In this embodiment, the second light-emitting layer 32 is composed of the composite material. Since the second light-emitting layer 32 and the first light-emitting layer 31 both contain the quantum dots, and the n-type metal oxide contained is also an electronic functional material, the interface contact between the second light-emitting layer 32 and the electronic functional layer 40 and the interface contact with the first light-emitting layer 31 are also improved, and the negative impact of the interface on electron injection and transmission is reduced, thereby improving the luminous efficiency of the light-emitting device 100.

[0096] In one embodiment, the electronic functional layer 40 may include one or both of an electron injection layer 41 and an electron transport layer 42; when the electronic functional layer 40 includes the electron injection layer 41 and the electron transport layer 42, the electron injection layer 41 is arranged close to the second electrode 20, and the electron transport layer 42 is arranged close to the light-emitting layer 30, and the material of the electron transport layer 42 includes the composite material.

[0097] In one embodiment, the material of the electron transport layer 42 includes doped or undoped inorganic nanocrystals, wherein the undoped inorganic nanocrystals are selected from one or more of ZnO, TiO2, SnO2, Al2O3, GaO, SiO2, Ga2O3, ZrO2, NiO, ZnS, ZnSe, CdS, InP, GaP, BaTiO3, Cs2CO3, Rb2CO3, RbBr, LiF, LiF / Yb, MgP, and MgF2; the doped inorganic nanocrystals include the undoped inorganic nanocrystals and doping elements, and the doping elements are selected from one or more of Mg, Ca, Li, Ga, Al, Co, Mn, Zr, W, Ti, and Y. In one embodiment, in one embodiment, the thickness of the electron transport layer 42 can be 20 to 40 nm, specifically 20 to 35 nm, 25 to 35 nm, 25 to 30 nm, 20 to 25 nm, 35 to 40 nm, etc.

[0098] In one embodiment, the material of the electron injection layer 41 can be a material known in the art for electron injection layer, for example, it can be selected from but not limited to at least one of LiF, MgP, MgF2, Al2O3, Ga2O3, LiF / Yb, ZnO, Cs2CO3, RbBr, and Rb2CO3.

[0099] In one embodiment, the light emitting device 100 may further include a hole functional layer 50, and the hole functional layer 50 is disposed between the first electrode 10 and the light emitting layer 30. The hole functional layer 50 may include a hole injection layer 51 and / or a hole transport layer 52. When the hole functional layer 50 includes two layers, the hole injection layer 51 and the hole transport layer 52, the hole injection layer 51 is disposed close to the first electrode 10, and the hole transport layer 52 is disposed close to the light emitting layer 30. The thickness of the hole injection layer 51 may be 20 to 200 nm, specifically 20 to 150 nm, 80 to 150 nm, 80 to 120 nm, etc. The thickness of the hole transport layer 52 may be 30 to 180 nm, specifically 30 to 150 nm, 50 to 150 nm, 50 to 120 nm, 80 to 120 nm, 80 to 100 nm, etc.

[0100] The material of the hole transport layer 52 is selected from arylamine, polyaniline, polypyrrole, poly(p-phenylene vinylene) and its derivatives, 4,4'-bis(p-carbazolyl)-1,1'-biphenyl compound, N,N,N',N'-tetraarylbenzidine, PEDOT:PSS and its derivatives, poly(N-vinylcarbazole) (PVK) and its derivatives, polymethacrylate and its derivatives, poly(9,9-octylfluorene) and its derivatives, poly(spirofluorene) and its derivatives, doped or undoped NiO, MoO3, WO3, V2O5, CrO3, CuO, MoS2, MoSe2, WS3, WS e3, CuS, CuSCN; wherein the aromatic amine is selected from 4,4'-di(9-carbazole)biphenyl (CBP), poly(9,9-dioctylfluorene-CO-N-(4-butylphenyl)diphenylamine) (TFB), poly(N,N'-bis(4-butylphenyl)-N,N'-bis(phenyl)benzidine) (poly-TPD), N,N'-di(4-(N,N'-diphenyl-amino)phenyl)-N,N'-diphenylbenzidine (DNTPD), poly(9,9-dioctylfluorene-co-bis-N,N-phenyl-1,4-phenylenediamine) (PFB), 4,4' ,4"-tri(carbazol-9-yl)triphenylamine (TCATA), 4,4',4"-tri(N-carbazol-9-yl)triphenylamine (TCTA), 4,4',4"-tri(N-3-methylphenyl-N-phenylamino)triphenylamine (m-MTDATA), N,N'-diphenyl-N,N'-bis(1-naphthyl)-1,1'-biphenyl-4,4"-diamine (α-NPD), N,N'-diphenyl-N,N'-bis(3-methylphenyl)-1,1'-biphenyl-4,4'-diamine (TPD), N,N'-diphenyl-N,N'-(1-naphthyl)-1,1'-biphenyl-4,4'-diamine (TPD), ,4'-diamine (NPB), Spiro-NPB, Spiro-TPD, N,N'-bis(3-methylphenyl)-N,N'-bis(phenyl)-spiro(spiro-TPD), spiro-NPB or one or more thereof; the poly(p-)phenylene vinylene and its derivatives are selected from one or more of poly(phenylene vinylene) (PPV), poly[2-methoxy-5-(2-ethylhexyloxy)-1,4-phenylene vinylene] (MEH-PPV) and poly[2-methoxy-5-(3',7'-dimethyloctyloxy)-1,4-phenylene vinylene] (MOMO-PPV).

[0101] The material of the hole injection layer 51 is a material having hole injection capability, selected from poly(ethylenedioxythiophene):polystyrene sulfonate (PEDOT:PSS), 2,3,5,6-tetrafluoro-7,7',8,8'-tetracyanoquinone-dimethane (F4-TCNQ), 2,3,6,7,10,11-hexacyano-1,4,5,8,9,12-hexaazatriphenylene (HATCN), copper phthalocyanine (CuPc ), poly(9,9-dioctyl-fluorene-co-N-(4-butylphenyl)-diphenylamine) (TFB), polyarylamine, poly(N-vinylcarbazole), polyaniline, polypyrrole, N,N,N',N'-tetrakis(4-methoxyphenyl)-benzidine (TPD), 4-bis[N-(1-naphthyl)-N-phenyl-amino]biphenyl (α-NPD), 4,4',4"-tris[phenyl(m-tolyl)amino]triphenylamine (m-MTDATA), 4,4',4"-tri(N-carbazolyl)-triphenylamine (TCTA), 1,1-bis[(di-4-tolylamino)phenylcyclohexane (TAPC), 4,4',4"-tri(diphenylamino)triphenylamine (TDATA) doped with F4-TCNQ, p-doped phthalocyanine (e.g., F4-TCNQ-doped zinc phthalocyanine (ZnPc)), F4-TCNQ-doped N,N'-diphenyl-N,N'-di(1-naphthyl)-1,1'-biphenyl-4,4"-diamine (α-NPD), transition metal oxides, transition metal sulfur compounds; wherein the transition metal oxides include one or more of NiO, MoO3, WO3, CuO; the metal sulfur compounds include one or more of MoS3, MoSe3, WS3, WSe3, CuS.

[0102] In one embodiment, the first electrode 10 and the second electrode 20 are independently selected from metal electrodes, carbon electrodes, doped or undoped metal oxide electrodes and composite electrodes; wherein the material of the metal electrode is selected from at least one of Al, Ag, Cu, Mo, Au, Ba, Ca, Ni, Ir and Mg; the material of the carbon electrode is selected from at least one of graphite, carbon nanotubes, graphene and carbon fiber; the material of the doped or undoped metal oxide electrode is selected from ITO, FTO, ATO, AZO, GZO, IZO, MZO, I At least one of TZO, ICO, AMO, SnO2, In2O3, Cd:ZnO, F:SnO2, In:SnO2, and Ga:SnO2; the material of the composite electrode is selected from at least one of AZO / Ag / AZO, AZO / Al / AZO, ITO / Ag / ITO, ITO / Al / ITO, ZnO / Ag / ZnO, ZnO / Al / ZnO, TiO2 / Ag / TiO2, TiO2 / Al / TiO2, ZnS / Ag / ZnS, and ZnS / Al / ZnS. Wherein, " / " represents a stacked structure, for example, the composite electrode AZO / Ag / AZO represents an electrode of a composite structure of three layers stacked together consisting of an AZO layer, an Ag layer, and an AZO layer. Wherein, the first electrode 10 and the second electrode 20 are a pair of electrodes. In one embodiment, the first electrode 10 is an anode, and the second electrode 20 is a cathode.

[0103] The light emitting device 100 further includes a substrate (not shown), which may also be referred to as a substrate. The substrate may be a rigid substrate or a flexible substrate. The rigid substrate may be a ceramic material or various glass materials. The flexible substrate may be a substrate formed of materials such as polyimide film (PI) and its derivatives, polyethylene naphthalate (PEN), phosphoenolpyruvic acid (PEP) or diphenylene ether resin. In one embodiment, the material of the substrate includes glass, silicon wafer, polycarbonate, polymethyl methacrylate, polyethylene terephthalate, polyethylene naphthalate, polyamide, polyether sulfone, or a combination thereof.

[0104] It can be understood that the light emitting device 100 can be an upright light emitting device or an inverted light emitting device. When the light emitting device 100 is an upright light emitting device, the substrate is combined with a side of the first electrode 10 away from the light emitting layer 30. When the light emitting device 100 is an inverted light emitting device, the substrate is combined with a side of the second electrode 20 away from the light emitting layer 30.

[0105] It is understandable that, in addition to the above-mentioned functional layers, the light-emitting device 100 may also be provided with some functional layers conventionally used in light-emitting devices to help improve the performance of the light-emitting device, such as an electron blocking layer, an electron injection layer, a hole blocking layer and / or an interface modification layer.

[0106] It can be understood that the material and thickness of each layer of the light-emitting device 100 can be set and adjusted accordingly according to the light-emitting requirements of the light-emitting device 100 .

[0107] The present application also provides a method for preparing a light emitting device, see Figure 3 , Figure 3 The present invention provides a flow chart of a method for preparing a light-emitting device according to an embodiment of the present invention, which specifically includes the following steps:

[0108] Step S21: providing a preset device, wherein the preset device includes a first electrode;

[0109] Step S22: arranging a light-emitting material on the preset device to form a light-emitting layer;

[0110] Step S23: forming a second electrode on the light-emitting layer to obtain a light-emitting device.

[0111] The first electrode is an anode, and the second electrode is a cathode. The light emitting device prepared in this embodiment is a positive device.

[0112] In one embodiment, the light-emitting device includes an electronic functional layer, and the step S23 specifically includes: forming the electronic functional layer and the second electrode on the light-emitting layer.

[0113] In one embodiment, the light-emitting device includes a hole functional layer, and the step S21 specifically includes: providing a prefabricated device, wherein the prefabricated device includes a stacked first electrode and a hole functional layer.

[0114] See also Figure 4 , Figure 4 This is a flow chart of another embodiment of a method for preparing a light-emitting device provided in the present application. The method for preparing a light-emitting device in this embodiment comprises the following steps:

[0115] Step S31: providing a prefabricated device, wherein the prefabricated device includes a second electrode;

[0116] Step S32: arranging a light-emitting material on the preset device to form a light-emitting layer;

[0117] Step S33: forming a first electrode on the light-emitting layer to obtain a light-emitting device.

[0118] The first electrode is an anode, and the second electrode is a cathode. The light emitting device prepared in this embodiment is an inverted device.

[0119] In one embodiment, the light emitting device includes an electronic functional layer, and the step S31 is specifically: providing a prefabricated device, wherein the prefabricated device includes a second electrode and an electronic functional layer. In one embodiment, the light emitting device includes a hole functional layer, and the step S33 is specifically: forming a hole functional layer and a first electrode on the light emitting layer.

[0120] In the above two embodiments, the luminescent material includes the composite material provided in the present application, or includes a composite material obtained by the method for preparing the composite material provided in the present application. For details, please refer to the relevant description above, which will not be repeated here. In a specific embodiment, the luminescent material is the composite material provided in the present application, or is a composite material obtained by the method for preparing the composite material provided in the present application.

[0121] In one embodiment, in step S22 and step S32, the composite material may be disposed on the prefabricated device by a solution method. Specifically, the solution method may be a spin coating method, a printing method, an inkjet printing method, a doctor blade method, a printing method, a dip-coating method, a soaking method, a spray coating method, a roll coating method, a casting method, a slit coating method, a strip coating method, and the like.

[0122] In a specific embodiment, in step S22 and step S32, arranging the luminescent material on the preset device to form a luminescent layer includes: arranging a third mixture on the preset device, wherein the third mixture includes the composite material and a third solvent.

[0123] Specifically, the third solvent may include one or more of an alcohol solvent, an ether solvent, tetrahydrofuran, acetone, chlorobenzene, and toluene. Specifically, the alcohol solvent includes one or more of methanol, ethanol, ethylene glycol, isopropanol, and n-butanol. Ether solvents include one or more of methyl ether and ethyl ether. Further, the concentration of the composite material in the third mixture may be 10 to 40 mg / mL, specifically 15 to 40 mg / mL, 15 to 35 mg / mL, 20 to 35 mg / mL, 20 to 30 mg / mL, 25 to 30 mg / mL, and the like.

[0124] After the third mixture is prepared by the solution method, it is necessary to dry it to remove the third solvent. The drying can be heating drying or vacuum drying. The heating drying temperature can be 60 to 80°C and the time can be 20 to 60 minutes. The vacuum drying pressure is 10 -1 ~10 -2 Pa. Furthermore, the vacuum drying temperature may be room temperature (about 25° C.).

[0125] In one embodiment, in step S22, arranging a luminescent material on the preset device to form a luminescent layer includes: arranging quantum dots on the preset device to form a first luminescent layer; and arranging a composite material on the first luminescent layer to form a second luminescent layer.

[0126] In one embodiment, in step S32, arranging a luminescent material on the preset device to form a luminescent layer includes: arranging a composite material on the preset device to form a second luminescent layer; and arranging quantum dots on the second luminescent layer to form a first luminescent layer.

[0127] In the above two embodiments, the formed light-emitting layer includes a first light-emitting layer close to the first electrode, and a second light-emitting layer close to the second electrode.

[0128] In one embodiment, the formation of the first light-emitting layer and the second light-emitting layer are both provided by a solution method. When the first light-emitting layer and the second light-emitting layer are provided by a solution method, the solvent of one layer uses a solvent with a strong solubility such as toluene and chlorobenzene, and the other layer uses a non-polar solvent such as n-octane and n-hexane, that is, the solvents in the process of the first light-emitting layer and the second light-emitting layer are orthogonal, thereby reducing the mutual solubility between the first light-emitting layer and the second light-emitting layer. In other embodiments, the composite material can also be provided on the prefabricated device by other methods known in the art, such as sputtering.

[0129] In each embodiment of the above-mentioned preparation method, the electron transport layer, hole functional layer, light-emitting layer, first electrode, second electrode, etc. can refer to the corresponding description of the light-emitting device 100 in the above text, and will not be repeated here.

[0130] In the light-emitting device provided in the present application, the preparation methods of the first electrode, the second electrode, the light-emitting layer, the hole functional layer, the electron functional layer and other film layers can be implemented by conventional techniques in the art, such as chemical methods or physical methods. Among them, the chemical method includes chemical vapor deposition, continuous ion layer adsorption and reaction method, anodization method, electrolytic deposition method, and coprecipitation method. The physical method includes physical plating method and solution method, among which the physical plating method includes: thermal evaporation coating method, electron beam evaporation coating method, magnetron sputtering method, multi-arc ion plating method, physical vapor deposition method, atomic layer deposition method, pulsed laser deposition method, etc.; the solution method can be spin coating, printing method, inkjet printing method, blade coating method, printing method, dip pulling method, immersion method, spraying method, roll coating method, casting method, slit coating method and strip coating method, etc.

[0131] It is understood that the method for preparing the light-emitting device may further include a packaging step, and the packaging material used for packaging may be selected from at least one of UV glue, metal film, and glass glue. In a specific embodiment, the packaging material may be acrylic resin or epoxy resin. The packaging may be machine packaging or manual packaging, and may be sealed with ultraviolet curing glue. The concentration of oxygen and water in the environment of the packaging step is less than 0.1ppm to ensure the stability of the light-emitting device.

[0132] The present application also relates to a display device, which includes the light-emitting device provided in the present application. The display device can be any electronic product with a display function, including but not limited to smart phones, tablet computers, laptop computers, digital cameras, digital video cameras, smart wearable devices, smart weighing electronic scales, car displays, televisions or e-book readers, wherein the smart wearable device can be, for example, a smart bracelet, a smart watch, a virtual reality (VR) helmet, etc.

[0133] The present application is described in detail below through specific embodiments. The following embodiments are only partial embodiments of the present application and are not limitations of the present application.

[0134] Embodiment 1:

[0135] This embodiment provides a method for preparing a composite material and the prepared composite material, wherein the preparation method specifically comprises the following steps:

[0136] Step 1: Step 3: Take 20 mg / mL red quantum dots (Cd 0.5 Zn 0.5 Se / ZnSe / ZnSeS / ZnS)-n-octane solution, to which triethylamine is added, and then the solution is placed under a 300W Xe lamp (full spectrum) for 1 hour under continuous stirring, during which it is carried out under the protection of circulating condensed water at 4°C; wherein the mass ratio of triethylamine to red quantum dots is 0.5:2.

[0137] Step 2: Under continuous illumination and stirring, 10 mg / mL of zinc p-toluenesulfonate n-octane was added dropwise to the solution of step 1, wherein the mass ratio of zinc p-toluenesulfonate to red quantum dots was 20:100; and continued irradiation and stirring for 3 hours, during which it was carried out under the protection of circulating condensed water at 4°C. After photodeposition, the above solution was washed three times by precipitation in excess ethyl acetate or acetone to wash away the excess zinc salt and obtain a composite material.

[0138] Embodiment 2:

[0139] This embodiment is substantially the same as Embodiment 1, except that in step 2, the mass ratio of zinc p-toluenesulfonate to red quantum dots is 40:100.

[0140] Embodiment 3:

[0141] This embodiment is substantially the same as Embodiment 1, except that in step 2, the mass ratio of zinc p-toluenesulfonate to red quantum dots is 60:100.

[0142] Embodiment 4:

[0143] This embodiment is substantially the same as embodiment 2, except that in step 2, zinc trifluoromethanesulfonate is used instead of zinc p-toluenesulfonate, and the irradiation is continued for 2 hours.

[0144] Embodiment 5:

[0145] This embodiment is basically the same as Embodiment 2, except that: in step 1, a red quantum dot-oleylamine solution is used instead of a red quantum dot-n-octane solution; in step 2, zinc trifluoromethanesulfonyl imide is used instead of zinc p-toluenesulfonate.

[0146] Embodiment 6:

[0147] This embodiment is basically the same as Embodiment 2, except that: in step 1, a red quantum dot-cyclohexane solution is used instead of a red quantum dot-n-octane solution; in step 2, difluoromethylsulfonyl zinc is used instead of zinc p-toluenesulfonate.

[0148] Embodiment 7:

[0149] This embodiment is substantially the same as embodiment 2, except that in step 2, zinc acetylacetonate and zinc trifluoromethanesulfonate (molar ratio 1:1) are used instead of zinc p-toluenesulfonate.

[0150] Embodiment 8:

[0151] This embodiment is substantially the same as embodiment 2, except that in step 2, zinc acetylacetonate is used instead of zinc p-toluenesulfonate.

[0152] Embodiment 9:

[0153] This embodiment is basically the same as embodiment 2, except that the green quantum dots (Cd 0.2 Zn 0.8 Se / Cd 0.6 Zn 0.4 Se / ZnSe / ZnS) instead of red quantum dots.

[0154] Embodiment 10:

[0155] This example is substantially the same as Example 9, except that in step 2, difluoromethylsulfonyl zinc is used instead of zinc p-toluenesulfonate.

[0156] Embodiment 11:

[0157] This embodiment is basically the same as embodiment 2, except that: the blue quantum dots (Cd 0.10 Zn 0.9 Se / Cd0.1Zn0.9Se / CdZnSe / ZnS), rather than red quantum dots.

[0158] Embodiment 12:

[0159] This embodiment is substantially the same as embodiment 11, except that in step 2, zinc acetylacetonate is used instead of zinc p-toluenesulfonate.

[0160] Embodiment 13:

[0161] This embodiment is substantially the same as Embodiment 2, except that in Step 2, tetrakis(2,4-pentanedione)titanium(IV) is used instead of zinc p-toluenesulfonate.

[0162] Embodiment 14:

[0163] This embodiment is substantially the same as embodiment 2, except that in step 2, tin trifluoromethanesulfonate is used instead of zinc p-toluenesulfonate.

[0164] Device Example 1

[0165] The device embodiment provides a quantum dot light emitting diode and a method for preparing the same, which specifically includes the following steps.

[0166] Step 1: Place the ITO glass sheet in a glass dish filled with ethanol solution, and ultrasonicate with acetone, deionized water, and ethanol for 20 minutes respectively, and then blow dry with a nitrogen gun; then place the cleaned ITO glass sheet in oxygen plasma for further cleaning for 10 minutes; continue to use UV-ozone to treat the surface of the ITO substrate for 15 minutes;

[0167] Step 2: Spin-coat the cleaned ITO glass sheet with PEDOT:PSS (thickness of about 25 nm) in air at a speed of 3500 r / min for 30 seconds; after spin coating, place it in air for annealing at 150°C for 30 minutes to obtain a hole injection layer; after annealing, quickly transfer the sheet to a glove box in a nitrogen atmosphere;

[0168] Step 3: Continue to spin-coat TFB (8 mg / mL, chlorobenzene solution) on the glass / ITO / PEDOT:PSS device at a speed of 3000 r / min for 30 seconds; after the spin coating is completed, anneal in a glove box at a temperature of 180°C for 30 minutes to obtain a hole transport layer with a thickness of 30 nm;

[0169] Step 4: Spin-coat the red quantum dot-n-octane solution (10 mg / mL) in Example 1 on the hole transport layer at a spin-coating speed of 1500 r / min for 45 seconds; anneal in a glove box at 60 degrees Celsius for 5 minutes to obtain a first light-emitting layer with a thickness of 20 nm;

[0170] Step 5: Spin coating the composite material of Example 1-chlorobenzene solution (10 mg / mL) on the first light-emitting layer at a spin coating speed of 2000 r / min for 30 seconds; after spin coating, annealing was performed in a glove box at 60 degrees Celsius for 5 minutes to obtain a second light-emitting layer with a thickness of 20 nm;

[0171] Step 6: Spin-coat the second light-emitting layer with a ZnO solution (30 mg / mL, ethanol solution) at a rotation speed of 3000 r / min for 30 seconds to obtain an electron transport layer with a thickness of 30 nm.

[0172] Step 7: Place the sample obtained in step 6 into a vacuum chamber, evaporate a top silver electrode on the light-emitting layer, the thickness of the silver electrode is 100 nm, and encapsulate it.

[0173] Device Examples 2-14

[0174] Device Example 2-14 is substantially the same as Device Example 1, with the only difference being that in step 5, the composite material of Example 2-14 is used.

[0175] Device Example 15

[0176] This device embodiment is basically the same as device embodiment 1, and the only difference is that step 4 is not performed, that is, the light-emitting device only includes the second light-emitting layer, and does not include the first light-emitting layer.

[0177] Device Example 16

[0178] This device embodiment is basically the same as device embodiment 1, with the only difference being that step 6 is not performed.

[0179] Device Example 17

[0180] This device embodiment is basically the same as device embodiment 1, except that step 4 and step 6 are not performed.

[0181] Device Comparison Example 1

[0182] The device comparative example is basically the same as the device embodiment 1, except that the n-octane solution of the red quantum dots in embodiment 1 is directly used to perform step 4 and step 5 is not performed.

[0183] Device Comparison Example 2

[0184] The device comparative example is basically the same as the device embodiment 1, except that the n-octane solution of the green quantum dots in embodiment 9 is directly used to perform step 4 and step 5 is not performed.

[0185] Device Comparison Example 3

[0186] The device comparative example is basically the same as the device embodiment 1, except that the n-octane solution of the blue quantum dots in embodiment 11 is directly used to perform step 4 and step 5 is not performed.

[0187] Test 1:

[0188] The quantum dot light-emitting diodes of device examples 1-17 and device comparative examples 1-3 were tested for external quantum efficiency EQE and lifetime, and the data are shown in Table 1. Figure 5-8 , Figure 5 EQE-J diagrams of device embodiments 1-8 and device comparative example 1, Figure 6 EQE-J diagrams of device examples 8 and 9 and device comparative example 2, Figure 7 EQE-J diagrams of device examples 11 and 12 and device comparative example 3, Figure 8 EQE-J diagrams of device embodiments 2, 13-17 and device comparative example 1.

[0189] (1) The detection method of external quantum efficiency EQE is:

[0190] The ratio of the number of electron-hole pairs injected into quantum dots to the number of emitted photons, expressed in %, is an important parameter for measuring the quality of electroluminescent devices and can be obtained by measuring with an EQE optical test instrument. The specific calculation formula is as follows:

[0191]

[0192] Among them, η e is the light output coupling efficiency, η γ is the ratio of the number of recombined carriers to the number of injected carriers, x is the ratio of the number of excitons that generate photons to the total number of excitons, K R is the radiation process rate, K NR is the rate of the non-radiative process.

[0193] Test conditions: carried out at room temperature, air humidity is 30-60%.

[0194] (2) The test method for life span T95@1000nit is: the time required for the brightness of the device to decrease to a certain proportion of the maximum brightness under constant current or voltage drive. The time when the brightness drops to 95% of the maximum brightness is defined as T95, and this life span is the measured life span. In order to shorten the test cycle, the device life span test is usually carried out at high brightness by accelerating device aging, and the life span at high brightness is obtained by fitting the extended exponential decay brightness attenuation fitting formula. For example, the life span at 1000nit is calculated as T95@1000nit. The specific calculation formula is as follows:

[0195]

[0196] Among them, T95 L For lifespan at low brightness, T95 H is the measured lifetime under high brightness, L H To accelerate the device to the highest brightness, L L is 1000nit, A is the acceleration factor, and this experiment measured the lifespan of several groups of QLED devices at rated brightness and found that the A value was 1.7.

[0197] Table 1

[0198] External quantum efficiency EQE (%) T95@1000nit(h) Device Example 1 12.81 4867.04 Device Example 2 14.39 5754.91 Device Example 3 13.30 5160.76 Device Example 4 13.87 5569.42 Device Example 5 14.00 5300.46 Device Example 6 13.98 5496.27 Device Example 7 14.09 5406.89 Device Example 8 13.92 5502.43 Device Example 9 22.61 21500.77 Device Example 10 20.93 20164.89 Device Example 11 18.56 208.67 Device Example 12 19.29 196.79 Device Example 13 14.28 5647.21 Device Example 14 14.16 5516.49 Device Example 15 13.97 5451.62 Device Example 16 13.24 5369.18 Device Example 17 12.98 5229.43 Device Comparison Example 1 11.67 3447.32 Device Comparison Example 2 14.96 15184.93 Device Comparison Example 3 14.23 115.02

[0199] From Table 1 and Figure 5-8 It can be seen that, relative to device comparative example 1, the red quantum dot devices of device embodiments 1-8, 13-17 all have good external quantum efficiency and lifespan, and relative to device comparative example 2, the green quantum dot devices of device embodiments 9 and 10 all have good external quantum efficiency and lifespan, and relative to device comparative example 3, the blue quantum dot devices of device embodiments 11 and 12 also all have good external quantum efficiency and lifespan. This shows that the composite material of the present application is used to prepare a light-emitting layer, and can have good electron transport and injection performance and light-emitting performance, and the corresponding light-emitting device has good external quantum efficiency and lifespan. When only the second light-emitting layer is included, that is, when the composite material is used as a single light-emitting layer, the light-emitting device can have good external quantum efficiency and lifespan while also reducing the manufacturing process of the light-emitting device and reducing the manufacturing cost.

[0200] The composite materials and their preparation methods, light-emitting devices and their preparation methods, and display devices provided in the embodiments of the present application are introduced in detail above. Specific examples are used herein to illustrate the principles and implementation methods of the present application. The description of the above embodiments is only used to help understand the methods and core ideas of the present application. At the same time, for technical personnel in this field, according to the ideas of the present application, there will be changes in the specific implementation methods and application scopes. In summary, the content of this specification should not be understood as a limitation on the present application.

Claims

1. A composite material, characterized in that: It includes an n-type metal oxide and quantum dots, wherein the surface of the quantum dots is connected with a negatively charged organic group; Wherein, the organic group includes one or more of the following structural formulas: Wherein, each occurrence of R1, R2, R3, and R4 is independently selected from one or more of H, D, -NH2, C1-C30 alkyl, aryl having 5-30 ring atoms, heteroaryl having 5-30 ring atoms, and C1-C30 alkyl substituted by at least one of -NO2, -CN, -NH2, -OH, -X, and C1-C5 alkyl, aryl having 5-30 ring atoms substituted by at least one of -NO2, -CN, -NH2, -OH, -X, and C1-C5 alkyl, and heteroaryl having 5-30 ring atoms substituted by at least one of -NO2, -CN, -NH2, -OH, -X, and C1-C5 alkyl.

2. The composite material according to claim 1, characterized in that Each occurrence of R1, R2, R3, and R4 is independently selected from -NH2, C1-C10 alkyl, C1-C10 alkyl substituted by at least one of -NO2, -CN, -NH2, -OH, -X, and C1-C5 alkyl, and aryl having 5-24 ring atoms substituted by at least one of -NO2, -CN, -NH2, -OH, -X, and C1-C5 alkyl.

3. The composite material according to claim 2, characterized in that The organic group includes one or more of the following structural formulas:

4. The composite material according to any one of claims 1 to 3, characterized in that The n-type metal oxide includes a doped or undoped first metal oxide, the undoped first metal oxide includes one or more of zinc oxide, titanium dioxide, and tin dioxide, the doped first metal oxide includes the undoped first metal oxide and a doping element, and the doping element includes one or more of Mg, Ca, Li, Ga, Al, Co, Mn, Zr, W, Ti, and Y; And / or, the quantum dots are selected from at least one of single structure quantum dots, core-shell structure quantum dots and perovskite semiconductor materials, the single structure quantum dots are selected from at least one of II-VI group compounds, IV-VI group compounds, III-V group compounds and I-III-VI group compounds, the II-VI group compounds are selected from CdS, CdSe, CdTe, ZnS, ZnSe, ZnTe, ZnO, HgS, HgSe, HgTe, CdSeS, CdSeTe, CdSTe, ZnSeS, ZnSeTe, ZnSTe, HgSeS, HgSeTe, HgSTe, CdZnS, CdZnSe, CdZnTe, CdHgS, Cd At least one of CdHgSe, CdHgTe, HgZnS, HgZnSe, HgZnTe, CdZnSeS, CdZnSeTe, CdZnSTe, CdHgSeS, CdHgSeTe, CdHgSTe, HgZnSeS, HgZnSeTe and HgZnSTe, the IV-VI group compound is selected from at least one of SnS, SnSe, SnTe, PbS, PbSe, PbTe, SnSeS, SnSeTe, SnSTe, PbSeS, PbSeTe, PbSTe, SnPbS, SnPbSe, SnPbTe, SnPbSSe, SnPbSeTe and SnPbSTe, the Group III-V compounds are selected from the group consisting of GaN, GaP, GaAs, GaSb, AlN, AlP, AlAs, AlSb, InN, InP, InAs, InSb, GaNP, GaNAs, GaNSb, GaPAs, GaPSb, AlNP, AlNAs, AlNSb, AlPAs, AlPSb, InNP, InNAs, InNSb, InPAs, InPSb, GaAlNP, GaAlNAs, GaAlNSb, GaAlPAs, GaAlPSb, GaInNP, GaInNAs, GaInNSb, GaInPAs, GaInPSb, InAlNP, InAlNAs, I At least one of nAlNSb, InAlPAs and InAlPSb, the I-III-VI group compound is selected from at least one of CuInS, CuInSe and AgInS; the core of the quantum dot with core-shell structure is selected from any one of the above-mentioned single structure quantum dots, and the shell material of the quantum dot with core-shell structure is selected from at least one of CdS, CdTe, CdSeTe, CdZnSe, CdZnS, CdSeS, ZnSe, ZnSeS and ZnS; the perovskite semiconductor material is selected from doped or undoped inorganic perovskite semiconductor, or organic-inorganic hybrid perovskite semiconductor; the general structural formula of the inorganic perovskite semiconductor is AMX3, wherein A is Cs + ion, M is a divalent metal cation selected from Pb 2+ Sn 2+ , Cu 2+ 、Ni 2+ 、Cd 2 + Cr 2+ , Mn 2+ 、Co 2+ , Fe 2+ ,Ge 2+ , Yb 2+ 、Eu 2+ At least one of, X is a halogen anion selected from Cl - Br - ,I - At least one of the following; the general structural formula of the organic-inorganic hybrid perovskite semiconductor is BMX3, wherein B is an organic amine cation selected from CH3(CH2) n-2 NH3 + or [NH3(CH2) n NH3] 2+ , where n≥2, M is a divalent metal cation selected from Pb 2+ Sn 2+ , Cu 2+ 、Ni 2+ 、Cd 2+ Cr 2+ , Mn 2+ 、Co 2+ , Fe 2+ ,Ge 2+ , Yb 2+ 、Eu 2+ At least one of, X is a halogen anion selected from Cl - Br - ,I - At least one of; and / or, the average particle size of the n-type metal oxide is 3 to 10 nm; And / or, the average particle size of the quantum dots is 2 to 15 nm; And / or, the mass ratio of the first metal oxide to the n-type metal oxide is (10-50):

100.

5. A method for preparing a composite material, characterized in that: include: Providing a first mixture, wherein the first mixture includes quantum dots and a first solvent, wherein the first solvent includes a hole sacrificial agent; After the first mixture is subjected to a first light treatment, an organic metal salt is added to the first mixture, and the mixture is subjected to a second light treatment to obtain a composite material; Wherein, the organic metal salt includes an organic anion and a metal ion, and the organic anion includes one or more of the following structural formulas: wherein each occurrence of R1, R2, R3, and R4 is independently selected from one or more of H, D, -NH2, C1-C10 alkyl, aryl having 5-24 ring atoms, heteroaryl having 5-24 ring atoms, and C1-C10 alkyl substituted with at least one of -NO2, -CN, -NH2, -OH, -X, and C1-C5 alkyl, aryl having 5-24 ring atoms substituted with at least one of -NO2, -CN, -NH2, -OH, -X, and C1-C5 alkyl, and heteroaryl having 5-24 ring atoms substituted with at least one of -NO2, -CN, -NH2, -OH, -X, and C1-C5 alkyl, and X is halogen; The metal ions include metal ions capable of forming an n-type metal oxide.

6. The preparation method according to claim 5, characterized in that: The quantum dots are selected from at least one of single structure quantum dots, core-shell structure quantum dots and perovskite semiconductor materials, the single structure quantum dots are selected from at least one of II-VI group compounds, IV-VI group compounds, III-V group compounds and I-III-VI group compounds, the II-VI group compounds are selected from CdS, CdSe, CdTe, ZnS, ZnSe, ZnTe, ZnO, HgS, HgSe, HgTe, CdSeS, CdSeTe, CdSTe, ZnSeS, ZnSeTe, ZnSTe, HgSeS, HgSeTe, HgSTe, CdZnS, CdZnSe, CdZnTe, CdHgS, CdHg The IV-VI group compound is selected from at least one of SnS, SnSe, SnTe, PbS, PbSe, PbTe, SnSeS, SnSeTe, SnSTe, PbSeS, PbSeTe, PbSTe, SnPbS, SnPbSe, SnPbTe, SnPbSSe, SnPbSeTe, SnPbSTe, and the II Group I-V compounds are selected from GaN, GaP, GaAs, GaSb, AlN, AlP, AlAs, AlSb, InN, InP, InAs, InSb, GaNP, GaNAs, GaNSb, GaPAs, GaPSb, AlNP, AlNAs, AlNSb, AlPAs, AlPSb, I nNP, InNAs, InNSb, InPAs, InPSb, GaAlNP, GaAlNAs, GaAlNSb, GaAlPAs, GaAlPSb, GaInNP, GaInNAs, GaInNSb, GaInPAs, GaInPSb, InAlNP, InAlNAs, In At least one of AlNSb, InAlPAs and InAlPSb, the I-III-VI group compound is selected from at least one of CuInS, CuInSe and AgInS; the core of the quantum dot with core-shell structure is selected from any one of the above-mentioned single structure quantum dots, and the shell material of the quantum dot with core-shell structure is selected from at least one of CdS, CdTe, CdSeTe, CdZnSe, CdZnS, CdSeS, ZnSe, ZnSeS and ZnS; the perovskite semiconductor material is selected from doped or undoped inorganic perovskite semiconductor, or organic-inorganic hybrid perovskite semiconductor; the general structural formula of the inorganic perovskite semiconductor is AMX3, wherein A is Cs + ion, M is a divalent metal cation selected from Pb 2+ Sn 2+ , Cu 2+ 、Ni 2+ 、Cd 2 + Cr 2+ , Mn 2+ 、Co 2+ , Fe 2+ ,Ge 2+ , Yb 2+ 、Eu 2+ At least one of, X is a halogen anion selected from Cl - Br - ,I - At least one of the following; the general structural formula of the organic-inorganic hybrid perovskite semiconductor is BMX3, wherein B is an organic amine cation selected from CH3(CH2) n-2 NH3 + or [NH3(CH2) n NH3] 2+ , where n≥2, M is a divalent metal cation selected from Pb 2+ Sn 2+ , Cu 2+ 、Ni 2+ 、Cd 2+ Cr 2+ , Mn 2+ 、Co 2+ , Fe 2+ ,Ge 2+ , Yb 2+ 、Eu 2+ At least one of, X is a halogen anion selected from Cl - Br - ,I - At least one of; and / or, the concentration of the quantum dots in the first mixture is 10 to 40 mg / mL; And / or, the hole sacrificial agent includes one or more of acetonitrile, triethylamine, triethanolamine, sodium sulfite, methanol, ethanol, and lactic acid; And / or, the mass ratio of the hole sacrificial agent to the quantum dots is (0.5-1.5):5; And / or, the mass ratio of the organic metal salt to the quantum dots is (1-3):5; And / or, the organic anion comprises one or more of the following structural formulas: And / or, the metal ions include one or more of zinc ions, titanium ions, tin ions, and Mg 2+ , Ca 2+ , Li + , Ga 3+ 、Al 3+ 、Co 2+ , Mn 2+ 、Zr 2+ , W 6+ 、Ti 4+ , Y + One or more of; And / or, the first solvent also includes one or more of C1-C5 halogenated alkanes, C5-C18 alkanes, C5-C18 olefins, C5-C18 fatty acids, and C5-C18 amine solvents.

7. The preparation method according to claim 5 or 6, characterized in that: The first light treatment adopts full spectrum irradiation; And / or, the first light treatment lasts for 1 to 2 hours; and / or, during the first light treatment of the first mixture, the temperature of the first mixture is maintained at 0-30° C.; and / or, during the first light irradiation process, the first mixture is in a stirring state; And / or, the second light treatment uses full spectrum irradiation; And / or, the second light treatment time is 2 to 4 hours; And / or, after adding the first organic metal salt to the first mixture, a second mixture is obtained, and during the second light treatment of the second mixture, the temperature of the second mixture is maintained at 0-30° C. and the second mixture is in a stirring state.

8. A light emitting device, characterized in that: include: A first electrode and a second electrode arranged opposite to each other; A second light-emitting layer is disposed between the first electrode and the second electrode; Wherein, the material of the second light-emitting layer includes the composite material as described in any one of claims 1 to 4, or includes the composite material prepared by the preparation method of the composite material as described in any one of claims 5 to 8.

9. The light emitting device according to claim 8, characterized in that: The light emitting device further comprises a first light emitting layer, wherein the first light emitting layer is disposed between the first electrode and the second light emitting layer; Wherein, the material of the first light-emitting layer is first quantum dots.

10. The light emitting device according to claim 9, characterized in that: The type of the first quantum dots is the same as the type of the quantum dots in the composite material in the second light-emitting layer; and / or, the thickness of the first light-emitting layer is 10 to 20 nm; And / or, the thickness of the second light-emitting layer is 20-30 nm. And / or, the first electrode and the second electrode are independently selected from metal electrodes, carbon electrodes, doped or undoped metal oxide electrodes and composite electrodes; wherein the material of the metal electrode is selected from at least one of Al, Ag, Cu, Mo, Au, Ba, Ca, Ni, Ir and Mg; the material of the carbon electrode is selected from at least one of graphite, carbon nanotubes, graphene and carbon fiber; the material of the doped or undoped metal oxide electrode is selected from ITO, FTO, ATO, AZO, GZO, IZO, MZO, IT At least one of ZO, ICO, AMO, SnO2, In2O3, Cd:ZnO, F:SnO2, In:SnO2, and Ga:SnO2; the material of the composite electrode is selected from one of AZO / Ag / AZO, AZO / Al / AZO, ITO / Ag / ITO, ITO / Al / ITO, ZnO / Ag / ZnO, ZnO / Al / ZnO, TiO2 / Ag / TiO2, TiO2 / Al / TiO2, ZnS / Ag / ZnS, and ZnS / Al / ZnS; And / or, the light-emitting device includes an electronic functional layer, the electronic functional layer is arranged between the second electrode and the second light-emitting layer, the electronic functional layer includes one or both of an electron injection layer and an electron transport layer, and the material of the electron transport layer includes doped or undoped inorganic nanocrystals, wherein the undoped inorganic nanocrystals are selected from ZnO, TiO2, SnO2, Al2O3, GaO, SiO2, Ga2O3, ZrO2, NiO, ZnS, ZnSe, CdS, InP, GaP, BaTiO3, Cs2CO 3. One or more of Rb2CO3, RbBr, LiF, LiF / Yb, MgP, and MgF2; the doped inorganic nanocrystals include the undoped inorganic nanocrystals and doping elements, and the doping elements are selected from one or more of Mg, Ca, Li, Ga, Al, Co, Mn, Zr, W, Ti, and Y; the material of the electron injection layer includes one or more of LiF, MgP, MgF2, Al2O3, Ga2O3, LiF / Yb, ZnO, Cs2CO3, RbBr, and Rb2CO3; And / or, the light-emitting device further comprises a hole functional layer, the hole functional layer is arranged between the first electrode and the second light-emitting layer, and the hole functional layer comprises one or both of a hole injection layer and a hole transport layer; wherein the material of the hole transport layer is selected from aromatic amines, polyaniline, polypyrrole, poly(p-)phenylene vinylene and its derivatives, 4,4'-bis(p-carbazolyl)-1,1'-biphenyl compounds, N,N,N',N'-tetraaryl benzidine, PEDOT:PSS and its derivatives, poly(N-vinyl carbazole) and its derivatives, polymethacrylate and its derivatives, Poly(9,9-octylfluorene) and its derivatives, poly(spirofluorene) and its derivatives, doped or undoped NiO, MoO3, WO3, V2O5, CrO3, CuO, MoS2, MoSe2, WS3, WSe3, CuS, CuSCN or one or more thereof; wherein the aromatic amine is selected from 4,4'-bis(9-carbazole)biphenyl, poly(9,9-dioctylfluorene-CO-N-(4-butylphenyl)diphenylamine), poly(N,N'-bis(4-butylphenyl)-N,N'-bis(phenyl)benzidine), N,N'-bis(4-(N,N'-diphenyl)- triphenylamine, 4,4',4"-tri(carbazol-9-yl)triphenylamine, 4,4',4"-tri(N-carbazolyl)triphenylamine, 4,4',4"-tri(N-3-methylphenyl-N-phenylamino)triphenylamine, N,N'-diphenyl-N,N'-bis(1-naphthyl)-1,1'-biphenyl-4,4"-diamine, N,N'-diphenyl-N,N'-bis(3-methylphenyl)-1,1'-biphenyl-4,4'-diamine, N,N One or more of '-diphenyl-N,N'-(1-naphthyl)-1,1'-biphenyl-4,4'-diamine, Spiro-NPB, Spiro-TPD, N,N'-bis(3-methylphenyl)-N,N'-bis(phenyl)-spiro, and Spiro-NPB; the poly(p-)phenylene vinylene and its derivatives are selected from one or more of poly(phenylene vinylene), poly[2-methoxy-5-(2-ethylhexyloxy)-1,4-phenylene vinylene] and poly[2-methoxy-5-(3',7'-dimethyloctyloxy)-1,4-phenylene vinylene];The material of the hole injection layer is selected from poly(ethylenedioxythiophene): polystyrene sulfonate, 2,3,5,6-tetrafluoro-7,7',8,8'-tetracyanoquinone-dimethane, 2,3,6,7,10,11-hexacyano-1,4,5,8,9,12-hexaazatriphenylene, copper phthalocyanine, poly(9,9-dioctyl-fluorene-co-N-(4-butylphenyl)-diphenylamine), polyarylamine, poly(N-vinylcarbazole), polyaniline, polypyrrole, N,N,N',N'-tetrakis(4-methoxyphenyl)-benzidine, 4-bis[N-(1-naphthyl)-N-phenyl-amino]biphenyl, 4,4',4"-tris[phenyl(m-tolyl)amino]triphenylamine, 4,4' ,4"-tri(N-carbazolyl)-triphenylamine (TCTA), 1,1-bis[(di-4-tolylamino)phenylcyclohexane, 4,4',4"-tri(diphenylamino)triphenylamine doped with F4-TCNQ, p-doped phthalocyanine, F4-TCNQ doped N,N'-diphenyl-N,N'-di(1-naphthyl)-1,1'-biphenyl-4,4"-diamine, transition metal oxides, transition metal sulfur compounds; wherein the transition metal oxides include one or more of NiO, MoO3, WO3, CuO; the metal sulfur compounds include one or more of MoS3, MoSe3, WS3, WSe3, CuS.;